Silica Application in Improving Growth and Production of Onion (Allium cepa L.) Under Drought Stress - Sembiring, Perdinanta; Ginting, Jonathan; Hanum, Hamidah; Hutabarat, Rina C. (Agro Bali : Agricultural Journal, 2025)
Climate change contributes to greater drought severity, leading to the decline of crop production. This study aims to evaluate the role of silica in onion production under water-deficient conditions.  The research was conducted at the Technical Implementation Unit Benih Induk Palawija in Tanjung Selamat, Deli Serdang, North Sumatra Province. Randomized Block Design with factorial arrangement was employed in this study, comprising 4 different doses of silica (0, 0.48, 0.96 and 1.44 g per plant) at 3 different levels of drought (40, 60 and 80% water holding capacity (WHC)).  The results showed that silica did not give significant results on vegetative growth and its yield, except for its root dry weight and plant wet weight. The best plant development was demonstrated by onions exposed to 80% WHC, followed by plants with 60% and 40% WHC.  The application of silica 0.48 g on onions treated with 60% WHC has a greater increase in the production of onion bulbs.